Unraveling proteomic signatures and neuroinflammatory networks in a CCI rat model of early sciatica: insights for neuropathic pain mechanisms - Li, Xingjuan; Wang, Xiaojie; Song, Jinhui; Jiang, Bin; Wen, Yaqin; Wang, Yang; Liu, Bo; Zheng, Xiao (Frontiers in Molecular Neuroscience, 2025)
IntroductionSciatica is a prevalent and highly debilitating condition that is clinically characterized by pain radiating along the distribution of the sciatic nerve. Despite its common occurrence, the progression of early sciatica remains not yet fully elucidated. The aim of this study is to explore the potential molecular mechanism underlying early-stage sciatica progression.MethodsA total of 20 rats were collected, with 9 in the control group and 11 rats in the chronic constriction injury (CCI) model group. The sciatic nerve tissues of rats were collected at three time points 1, 3, and 7 days post surgery. Protein microarray was used to detect the expression levels of 27 cytokines in sciatic nerve tissues at different times. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) were used for functional and pathway analysis of the differentially expressed proteins (DEPs). ELISA was used to detect the levels of chemokine CINC-2 and neurotrophic growth factors (CNTF).ResultsA total of 11 proteins showed significant differential expression between the CCI and control groups at all three time points (days 1, 3, and 7) after sciatic nerve injury. Specifically, Cytokine-Induced Neutrophil Chemoattractant-2 (CINC-2), Cytokine-Induced Neutrophil Chemoattractant-3 (CINC-3), Lipopolysaccharide-Induced CXC chemokine (LIX), Lymphocyte-Selectin (L-Selectin), Platelet-Derived Growth Factor-AA (PDGF-AA), Interleukin-1 alpha (IL-1α), Interleukin-6 (IL-6), Tissue Inhibitor of Metalloproteinase-1 (TIMP-1), and beta-Nerve Growth Factor (β-NGF) were significantly upregulated (p < 0.05), whereas the neurotrophic-related protein CNTF was significantly downregulated (p < 0.05). KEGG pathway analysis revealed that these DEPs were primarily enriched in key inflammatory signaling pathways, including the JAK–STAT, Cytokine-cytokine receptor interaction, Chemokine, Tumor Necrosis Factor (TNF), NOD-like receptor, and NF-kappa B signaling pathways. GO analysis indicated their involvement in biological processes such as immune response and cellular chemotaxis. Protein function analysis further confirmed the close correlation of these DEPs with cellular recognition and neuroinflammation. Additionally, ELISA validation showed that the key protein CINC-2 was upregulated and CNTF was significantly downregulated in the early CCI group.DiscussionThe progression of early sciatic is closely associated with neuroinflammation triggered by the overexpression of inflammatory factors and nerve dysfunction mediated by neurotrophic-related proteins.